CORPORATE SOCIAL RESPONSIBILITY OF BUSINESS IN THE REPUBLIC OF KAZAKHSTAN - А. Yerniyazova,; Zh. Smailova, (Academic Journal of Physical and Chemical Sciences, 2019)
Recently, in Kazakhstan, attention to such phenomenon as “corporate social responsibility” has increased. The problems of socially responsible business behavior, its role in the socio-economic development of the country, possibilities and effectiveness of interaction with the local community are widely discussed. This article reveals the importance of researching the basis of social responsibility in business, the practice of applying this concept both in Kazakhstan and abroad. The reasons for the insufficient development of social responsibility of domestic companies, most typical management problems in this area, as well as the issues of financing charitable and social activities of companies are considered. The possibilities and directions for improving the social responsibility of business in Kazakhstan are substantiated.